Legal Protection of The Parties in The Execution of Fiduciary Guarantees After The Decision of The Constitutional Court Number 71/Puu-Xix/2021 - Putu Ayu Sriasih Wesna; Anak Agung Ngurah Bhaskara Ananda Putra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The Constitutional Court has issued Decisions Number 18/PUU-XVII/2019, Number 2/PUU-XIX/2021, and Number 71/PUU-XIX/2021, in which the three decisions have a major impact on the special characteristics of fiduciary guarantees, namely the execution of guarantees that easy with parate execution. This research uses normative legal research methods. The results of this research are the Execution of Fiduciary Guarantees After the Constitutional Court Decision Number 71/PUU-XIX/2021 execution with parate execution becomes ineffective. The legal standing of the Fiduciary Giver is benefited, the Fiduciary Giver has legal protection over the execution parate of the fiduciary recipient. The legal standing of the Fiduciary Recipient is aggrieved due to the loss of legal certainty over the execution parate. The fiduciary recipient in his position as a creditor loses his legal protection in terms of making settlements for bad loans due to complicated execution conditions..